SELF-CONCEPT AMONG STROKE PATIENTS IN THE STROKE UNIT OF RSUD dr. SOEDOMO TRENGGALEK - Awan Hariyanto; Dita Putri Ariyanti (Indonesian Health Literacy Journal, 2026)
https://docs.google.com/document/d/1oEr50bBvuqH1-DXZfUnD6Lch3nVZeDW2/edit?usp=sharing&ouid=114103985896209439586&rtpof=true&sd=true